Differences in pre‐service teachers' knowledge and readiness to use ICT in education. (8th January 2018) - Valtonen, Teemu; Kukkonen, Jari; Kontkanen, Sini; Mäkitalo‐Siegl, Kati; Sointu, Erkko
Abstract: The aim of this paper is to provide insights into differences between pre‐service teachers based on the areas of technological pedagogical content knowledge (TPACK) and the areas of theory of planned behaviour (TPB) in the context of using information and communication technology in education. The target group consisted of 267 first‐year pre‐service teachers at 3 Finnish universities. Differences between pre‐service teachers were outlined using cluster analysis based on their knowledge of different TPACK areas (the respondents' weak and strong areas). To see how the TPB areas aligned with the 4 TPACK clusters, 1‐way analysis of variance was used. Statistically significant differences between the 4 clusters were found in all the TPB areas except subjective norms. These results provide insights into the differences among pre‐service teachers in the context of TPACK and the TPB. They also suggest that instead of considering pre‐service teachers as one homogenous group, we need to understand the variations among their abilities and knowledge in order to be able to provide them with support they need within teacher education. Lay Description: What is already known about this topic: TPACK is a well working framework for studying (pre‐service) teachers' knowledge related to the use of ICT in education Theory of planned behavior (TPB) is a valid framework for studying factors affecting pre‐service teachers' use of ICT in education The variation among strong and weak areas of TPACK and TPB have been indicated, still the target groups are mainly dealt as one homogenous group What this paper adds: Research outlines subgroups of pre‐service teachers based on TPACK There are strong differences among pre‐service teachers based on their assessment of their TPACK areas Importance of ICT in education is well understood among pre‐service teachers' Paper outlines relation between TPACK and TPB frameworks Implications for practice and/or policy: Differences of TPACK areas need to be better considered in teacher education In future studies it is important to consider the variation among pre‐service teachers related to areas of TPACK Paper outlines strong and weak areas of TPACK and TPB that need to be acknowledged in teacher training